EFEKTIFITAS BAWANG MERAH TERHADAP PENURUNAN SUHU TUBUH PADA ANAK FEBRIS USIA 1 â 5 TAHUN - Nugroho, Christianto (Jurnal AKP, 2012)
Fever are circumstances when individuals experiencing or at risk of increased body temperature continuously for more than 37.80 C (1000F) per oral or 38.90 C (1010F) per rectal due to external factors) lt can be said that normal body temperature when the temperature is 36.50 C - 37,50C. The purpose of this study is to determine the effectiveness of red onion to the decrease of body temperature in children aged 1-5 years with fever. The research design used in this study is "Pre-experimental", One-Group-Post-Pre-Design Test. Population of all children aged 1-5 years who have increased body temperature in the IHC Boegenvile 1 Hamlet Village Tertek Pare District as much as 56 respondents, eight respondents sample taken with accidental sampling technique. Data analysis was done by observation before and after treatment in April, 2010.From the results showed that body temperature before administration of body temperature prior onions were treated at 37.9750C after treatment of 37.5750 C, and the mean of the results of the settlement amounted to 0.4. Median body temperature and the mode of treatment was 380 C and body temperature after treatment was 37.6ÂºC. From the above description can be concluded that after being given a ground onion and smeared throughout the body, can be proven to decrease body temperature, which means onion effective in decreasing body temperature in children aged 1-5 years with feverÂ  Keywords: Fever, Onion